2000
DOI: 10.1016/s0014-5793(00)02042-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of resistance of normal cells to TRAIL induced apoptosis vary between different cell types

Abstract: Resistance of normal cells to tumour necrosis factor related apoptosis inducing ligand (TRAIL) induced apoptosis is believed to be mediated by expression of two decoy receptors. Here we show that the expression and localisation of TRAIL receptors (TRAIL-Rs) vary between different cells and that resistance to TRAIL is mediated by different mechanisms. The decoy receptor, TRAIL-R3, appeared important in protection of endothelial cells, whereas lack of surface death receptor expression and as yet unknown intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
136
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(148 citation statements)
references
References 32 publications
11
136
0
1
Order By: Relevance
“…If this is true, then negative TRAIL expression in CM cells in RT-PCR assays might explain their susceptibility to the TRAIL death pathway. Normal islet cells show susceptibility to the TRAIL death pathway after treatment by PI-PLC, consistent with a similar study using human normal umbilical vein endothelial cells as TRAIL target cells [40]. Treatment with PI-PLC could remove the TRAIL-R3 receptors from the cell membrane [11,40].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…If this is true, then negative TRAIL expression in CM cells in RT-PCR assays might explain their susceptibility to the TRAIL death pathway. Normal islet cells show susceptibility to the TRAIL death pathway after treatment by PI-PLC, consistent with a similar study using human normal umbilical vein endothelial cells as TRAIL target cells [40]. Treatment with PI-PLC could remove the TRAIL-R3 receptors from the cell membrane [11,40].…”
Section: Discussionsupporting
confidence: 87%
“…We have shown in this study that TRAIL-R1, -R2, -R3 and/or -R4 mRNA is expressed in normal primary TRAIL can induce apoptosis in a wide range of transformed cell lines but not in many normal cells, although the mRNAs of TRAIL-R1 and R2 were found to be widely expressed on normal tissue [40]. Similarly, most of the normal islet cells in this study are resistant to the TRAIL death pathway, although these cells express TRAIL receptors R1 and R2.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Both recombinant, soluble TRAIL and wild-type, membrane-bound TRAIL induce apoptosis in a wide variety of transformed cell lines via interaction with one or both of the death receptors DR4/TRAIL-R1 and DR5/TRAIL-R2, 12,13 which in turn initiates activation of caspase-8 through FADD, leading to apoptosis. [14][15][16] However, the antagonistic decoy receptors DcR1, 17,18 DcR2, 19 and osteoprotegerin 20 are believed to protect normal cells from the cytotoxic effects of TRAIL by competing with DR4/TRAIL-R1 and DR5/TRAIL-R2 for TRAIL binding.…”
Section: In Either Dld1/bax-r or Dld1/trail-r Cells Bcl-xl Expressiomentioning
confidence: 99%
“…Tumor necrosis factor (TNF)-a-related apoptosisinducing ligand (TRAIL), is a cytokine of TNF family and is capable of inducing apoptotic cell death in a variety of cancer type, while producing negligible effects on normal cells (Zhang et al, 2000;Ozawa et al, 2001;He et al, 2004). Studies have shown that some cancer cells are resistant to the apoptotic effects of TRAIL (Deeb et al, 2004;Yamaguchi et al, 2005;Hu et al, 2006), however, these cells can be sensitized by combination of TRAIL with different chemotherapeutic drugs, indicating that combinatorial approach can be utilized to overcome the resistance of cancer cells to TRAIL.…”
Section: Introductionmentioning
confidence: 99%